Growth and productivity of gobhi sarson (Brassica napus) cultivars under diverse sowing environments - BHAGAT, RAKSHIT; SINGH, MAHENDER; SHARMA, B C (The Indian Journal of Agricultural Sciences, 2022)
The sowing date of oilseed [winter (rabi) season] crop changes from year to year based on the harvesting of the preceding sown (rainy (kharif) season) crop in the northern regions of India, which exposes the crop to varying weather situations. So, to investigate the impact of sowing environments on growth, yield attributes and yield of gobhi sarson (Brassica napus L.) cultivars, an experiment was conducted with the 3 sowing environments and 3 cultivars under sub-tropical conditions of Jammu during the winter (rabi) season of 2018–19 and 2019–20. The pooled data of two years revealed that the early sown gobhi sarson crop recorded significantly highest growth parameters (plant height, leaf area index and dry matter accumulation) and yield attributes (number of primary and secondary branches/plant, siliquae/ plant and seeds/siliqua) as compared to the delayed sown crop. With the result (source sink relationship), significantly higher seed yield was recorded under the first sowing environment (1758 kg/ha) sown crop, while significant reduction to the extent of 27.66% and 66.95% was recorded with delayed sowing, D2 (1377 kg/ha) and D3 (1053 kg/ha), respectively. The cultivar GSL-1 recorded significantly higher plant height, LAI, dry matter, primary and secondary branches/plant, siliquae/plant, seeds/silique, followed by ONK-1 and DGS-1, resulting in significantly higher yield of GSL-1 (1493 kg/ha) over DGS-1 (1262 kg/ha) but at par with ONK-1 (1432 kg/ha).